Network Architecture and Key Technologies for the Integrated Satellite and Terrestrial Mobile Communication System - Hui XU; Deshan MIAO; Shaoli KANG; Shaohui SUN (天地一体化信息网络)
The fl exible and reconfi gurable network architecture for the integrated satellite and terrestrial mobile communication system was proposed based on analyzed the scenarios and requirements.And the integrated satellite and terrestrial mobile communication system could realized the reconstruction of network functions and ensured the deterministic service capability of the network.A unifi ed transmission mechanism and the mobility management mechanism for the integrated satellite and terrestrial mobile communication system was proposed to realized efficient transmission and improved network resource management effi ciency.